WdW review arts, culture, and journalism in revolt - Ayas, Defne 1976-; Kleinman, Adam 1978-; Khatib, Naim al (Witte de With Center for Contemporary Art, 2017)
This publication constitutes an anthology of essays, cartoons and image readings published on Witte de With's online magazine 'WdW Review'. Featured writers include Yanis Varoufakis, Kate Zambreno, Ana Teixeira Pinto, Ekaterina Degot, Quinn Latimer and others
Keywords: Geschichte 2013-2016; Kunst; Witte de With, centrum voor hedendaagse kunst; Art, Modern / 21st century; Art / Political aspects; 2000-2099